Children and Childhood in Colonial Nigerian Histories - Aderinto, S.; Aderinto, S. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
This book brings together the newest and the most innovative scholarship on Nigerian children—one of the least researched groups in African colonial history. It engages the changing conceptions of childhood, relating it to the broader themes about modernity, power, agency, and social transformation under imperial rule.